Keragaman Pola Hubungan Pabrikan-Pemasok dalam Pencapaian Kinerja Operasional - Supriharyanti, Elisabeth (Kajian Manajemen dan Bisnis, 2009)
The study examined the influence of four variables (market characteristic, product characteristic, supplier characteristic, social bond) on manufacturer-supplier relationship pattern. The result of hierarchical regression, indicated that product characteristic have positive significant effect on manufacturer-supplier relationship pattern Further, manufacturer-supplier relationship pattern was predictor significant of operational performance.